2014
DOI: 10.1093/jisesa/ieu123
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Bemisia Tabaci (Hemiptera: Aleyrodidae) to Several New Insecticides in China: Effects of Insecticide Type and Whitefly Species, Strain, and Stage

Abstract: Whitefly biotypes B and Q are the two most damaging members of the Bemisia tabaci (Hemiptera: Aleyrodidae) species complex. Control of B. tabaci (and especially of Q) has been impaired by resistance to commonly used insecticides. To find new insecticides for B. tabaci management in China, we investigated the sensitivity of eggs, larvae, and adults of laboratory strains of B and Q (named Lab-B and Lab-Q) and field strains of Q to several insecticides. For eggs, larvae, and adults of B. tabaci and for six insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 46 publications
3
39
1
2
Order By: Relevance
“…Previous field monitoring has indicated that the resistance to imidacloprid can be 23.4–1958 times greater in B. tabaci Q than in B . Nymphal and adult stages of a laboratory population of B. tabaci B were also much more susceptible than the same stages of a laboratory population of B. tabaci Q to all tested insecticides . In the present study, expression of CYP6CM1 and CYP6CX1 was not greater in Q than in B (supporting information Table S2), suggesting that the enzymes encoded by these genes may not explain the greater insecticide resistance of Q compared with B; these two enzymes may not be involved in insecticide resistance in Q versus B or may only be associated with imidacloprid resistance within the same B. tabaci biotype.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Previous field monitoring has indicated that the resistance to imidacloprid can be 23.4–1958 times greater in B. tabaci Q than in B . Nymphal and adult stages of a laboratory population of B. tabaci B were also much more susceptible than the same stages of a laboratory population of B. tabaci Q to all tested insecticides . In the present study, expression of CYP6CM1 and CYP6CX1 was not greater in Q than in B (supporting information Table S2), suggesting that the enzymes encoded by these genes may not explain the greater insecticide resistance of Q compared with B; these two enzymes may not be involved in insecticide resistance in Q versus B or may only be associated with imidacloprid resistance within the same B. tabaci biotype.…”
Section: Discussioncontrasting
confidence: 48%
“…In another study in China, B. tabaci Q strains showed moderate to strong resistance to imidacloprid, thiamethoxam and acetamiprid, while the single B. tabaci B strain in the study was susceptible to the investigated insecticides . Previous research from the present authors' laboratory indicated that a laboratory population of Q was less sensitive than a laboratory population of B to all insecticides tested; the resistance ratio of Q/B was as high as 206 …”
Section: Introductionmentioning
confidence: 40%
“…L −1 indicated a potentially high risk in using cyantraniliprole to control B. tabaci . Xie et al 51. also reported the inefficiency of cyantraniliprole against adult B. tabaci , although it was highly effective against eggs and larvae.…”
Section: Discussionmentioning
confidence: 99%
“…6), and further indicated that GST-d7 might play a role in the process of MEAM1's displacement by MED. Previous reports have also shown that B. tabaci MED has a higher tolerance than B. tabaci MEAM1 to nearly all used insecticides and especially to nicotinic insecticides like imidacloprid Rao et al, 2012;Xie et al, 2014a). Previous reports have also indicated that, since 2007, B. tabaci MED has been gradually replacing B. tabaci MEAM1 in China (Pan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…B. tabaci MED was first found in Yunnan Province, China, in 2003(Chu et al, 2006, and has now displaced the well-established populations of MEAM1 in most parts of China Teng et al, 2010;Pan et al, 2011Pan et al, , 2015. This displacement has been attributed to the higher tolerance of B. tabaci MED than B. tabaci MEAM1 to nearly all commonly used insecticides (Horowitz et al, 2005;Dennehy et al, 2010;Xie et al, 2014a;Pan et al, 2015). Although the molecular mechanism underlying this tolerance remains unclear, our previous report showed that the high tolerance of B. tabaci MED to pesticides is associated with enhanced expression of detoxification genes like cytochrome P450 monooxygenases (P450s), GSTs and carboxylesterase (CarE) (Guo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%